2013
DOI: 10.1515/applirev-2013-0016
|View full text |Cite
|
Sign up to set email alerts
|

The problematization of racial/ethnic minority student participation in U.S. study abroad

Abstract: Within U.S. higher education, there has been concern expressed about the underrepresentation of racial/ethnic minority students in U.S. study abroad programs. Though as a whole these students participate in study abroad at lower rates than their Caucasian counterparts, the fact that study abroad participation is even problematized by race/ethnicity (rather than other social categories such as gender, socioeconomic status or field of study) and the manner by which this is done warrant critical investigation. Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Their results indicated that both traditional and non-traditional community college students viewed SA positively as an opportunity to increase their academic transfer prospects, intercultural competence, and L2 proficiency, and that to achieve these personal-level factors, there was a need for faculty encouragement and parental and peer group support. Similar to the challenges encountered by marginalized participants from four-year institutions (Thomas, 2013), the community college students in Amani and Kim (2018) also noted concerns about funding, fear of travel, and anxiety about academic-life balance as barriers that they had to overcome to participate in SA.…”
Section: Research Taskmentioning
confidence: 85%
See 2 more Smart Citations
“…Their results indicated that both traditional and non-traditional community college students viewed SA positively as an opportunity to increase their academic transfer prospects, intercultural competence, and L2 proficiency, and that to achieve these personal-level factors, there was a need for faculty encouragement and parental and peer group support. Similar to the challenges encountered by marginalized participants from four-year institutions (Thomas, 2013), the community college students in Amani and Kim (2018) also noted concerns about funding, fear of travel, and anxiety about academic-life balance as barriers that they had to overcome to participate in SA.…”
Section: Research Taskmentioning
confidence: 85%
“…Investigating the experiences of these students can enhance our understanding of language learning during SA, highlight marginalized students' unique competencies and strengths (e.g., Doerr, 2020;Hartman et al, 2020;Perkins, 2020;Quan & Menard-Warwick, 2021), and inform our efforts to make SA a positive and equitable experience for all students. More research is needed to spotlight the voices of marginalized students, as previous authors have advocated (Anya, 2020;Lee & Green, 2016;Thomas, 2013). In addition, we argue that research on language-focused SA (i.e., SA programs with an L2 component) can benefit from adopting equity as a lens.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…This is partly due to social class, which goes beyond economic means to include one's social identity, or perception and access to material and symbolic goods, such as international travel, healthcare, technology, and education (Diao, 2021). Moreover, underrepresented students may be turned away by programming that does not address their interests or assumes a desire to engage with the wealthy embedded in representations of SA, which oftentimes also intersects with White cultural practices (Anya, 2017;Thomas, 2013). For example, traveling to encounter exotic customs and food reflects the fact that these cultural practices may only be exotic for White students with limited intercultural experiences.…”
Section: Underrepresentation Due To Socioeconomic Status and Social C...mentioning
confidence: 99%
“…Specifically, there was no research incorporating Black student voices, experiences, or perspectives on marketing efforts. Because Black students are uniquely positioned to articulate what they find to be inclusive, qualitative research that involves said students was necessary for higher education leaders to better understand what aspects of study abroad marketing materials resonate with Black students (Nguyen, 2015;Thomas, 2013). With that aim, this study examined how Black undergraduate students at predominantly White institutions described their experiences with study abroad marketing and recruitment efforts.…”
Section: Marketing and Study Abroadmentioning
confidence: 99%